Sources of European history since 1900 - Perry, Marvin; Berg, Matthew Paul, 1961-; Krukones, James H., 1951- (Boston, MA : Wadsworth, Cengage Learning, 2011)
This reader uses primary sources to illuminate the intellectual, political, and cultural history of Europe from 1900 to the present. Each part, chapter, and section contains an introduction that explains the historical seeing and significance of the readings within.
Western Europe: the dawn of a new era. The aftermath: devastation and hope ; The recent past and Western consciousness ; The new West Germany: democratic government, the Nazi past, and the economic miracle ; The Cold War -- The Eastern Bloc, 1945-1981. The'people's democracies' ; Repression in the Soviet Union and its satellites ; Dissidence and popular revolt ; Solidarity -- Western Europe since the 1960s. Social and cultural criticism ; Conflicting approaches to industrial relations ; The new right ; Ethnic minorities ; Coming to terms with the past: reflections on the Holocaust -- The collapse of Communism. A tottering old regime ; Popular protest and dissolution ; The trauma of transition from Communism -- Europe today. European Union: growing interdependence ; Anti-Americanism in contemporary Europe ; Russia: creeping autocracy and burgeoning nationalism ; Islam in Europe: failure of assimilation and the threat of terrorism ; The new anti-Semitism: old hatreds revived ; In defense of European values.
Keywords: Europe -- History -- 20th century -- Sources; Europe -- History -- 20th century